Resveratrol inhibits cadmium induced neuronal apoptosis by modulating calcium signalling pathway via regulation of MAPK/mTOR network (Bangladesh Journal of Pharmacology, 2015)
Cadmium, a toxic environmental contaminant, induces oxidative stress leading to various neurodegenerative disorders, where it interferes with homeos-tasis of intracellular free calcium ([Ca2+]i), leading to cellular damage and apoptosis. We investigated whether resveratrol, a plant-derived antioxidant could offer protection against cadmium-induced neuroapoptosis. Primary cortical neurons were exposed to cadmium (10 or 20 µM) with/without prior exposure to resveratrol (5, 10 or 20 µM) for 12 hours and unexposed cells served as control. Resveratrol caused marked reduction in cadmium-induced neuronal apoptosis and down-regulated caspase-3 expressions. Cadmium-induced marked elevations in reactive oxygen species, and ([Ca2+]i) levels were potentially reduced by resveratrol. Resveratrol effectively regulated the alterations observed in the activation levels of mitogen-activated protein kinases (MAPKs) and proteins of mammalian target of rapamycin (mTOR) pathways. Thus, resveratrol effectively protected the cortical neurons exposed to cadmium by modulating the ([Ca2+]i) levels and regulating the MAPK/mTOR pathways.